2020
DOI: 10.1016/j.celrep.2019.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Thermogenesis in Mice Is Enhanced by Opsin 3-Dependent Adipocyte Light Sensing

Abstract: Highlights d Adipocytes express encephalopsin (OPN3), a 480 nm bluelight-sensitive opsin d Mice lacking OPN3 or blue light have diminished thermogenesis during cold exposure d Loss of OPN3 reduces oxygen consumption and energy expenditure d White adipocyte OPN3 promotes lipolysis during cold exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 96 publications
(119 reference statements)
0
77
0
3
Order By: Relevance
“…OPN3 homologs in mosquito, pufferfish, zebrafish, and chicken absorb blue light (Koyanagi et al, 2013;Sugihara et al, 2016). Human OPN3, however, does not absorb visible light by UV-visible spectroscopy (Ozdeslik et al, 2019), despite several studies indicating OPN3-meditated blue light responses in mammals (Kato et al, 2016;Buscone et al, 2017;Barreto Ortiz et al, 2018;Regazzetti et al, 2018;Yoshimoto et al, 2018;Castellano-Pellicena et al, 2019;Nayak et al, 2020;Sato et al, 2020). In lower vertebrates, photosensitive areas in the diencephalon contain many light-responsive pigments and opsins that directly mediate physiological reactions like color change and motor responses independent of the eyes or pineal glands (Van Veen et al, 1976;Tabata, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OPN3 homologs in mosquito, pufferfish, zebrafish, and chicken absorb blue light (Koyanagi et al, 2013;Sugihara et al, 2016). Human OPN3, however, does not absorb visible light by UV-visible spectroscopy (Ozdeslik et al, 2019), despite several studies indicating OPN3-meditated blue light responses in mammals (Kato et al, 2016;Buscone et al, 2017;Barreto Ortiz et al, 2018;Regazzetti et al, 2018;Yoshimoto et al, 2018;Castellano-Pellicena et al, 2019;Nayak et al, 2020;Sato et al, 2020). In lower vertebrates, photosensitive areas in the diencephalon contain many light-responsive pigments and opsins that directly mediate physiological reactions like color change and motor responses independent of the eyes or pineal glands (Van Veen et al, 1976;Tabata, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the OPN3 knock-out mouse has a yet unidentified neurologic phenotype that does not manifest in the conditions or life span to which we house our mice. Indeed, the knock-out mouse was first generated years ago (Buhr et al, 2015), but it has just recently been discovered that only when perturbing normal living and physiological conditions does the OPN3 knock-out mouse exhibit diet-induced obesity and insulin resistance because of dysregulation of metabolic processes in brown adipocytes (Sato et al, 2020) and deficiency in thermogenesis under cold shock because of dysregulation of lipolysis in adipose tissue (Nayak et al, 2020). Interestingly, none of these phenotypes have demonstrated correlations to OPN3 expression in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Mice have been shown to express opsins in their skin, 15,56 as well as in their brain (Opn3 and Opn5), 57,58 testis (Opn5), 57 adipose tissue (Opn3), 59 vascular smooth muscle, 60,61 iris (Opn4), 62 and ciliary body (Opn5). 63 Recent work has suggested a photosensitive role for Opn3 in regulating metabolism in murine adipose tissue 59,64 and has demonstrated that Opn5 functions as a photopigment synchronizing circadian entrainment in skin in vivo. 12 Pulmonary arterial diameter has also recently been shown to be light sensitive and use an Opn4-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, we observed that higher levels of PA consistently corresponded to decreased adiposity. Interestingly, sunlight exposure was related to less subcutaneous fat but more visceral fat, which may be due to compensatory behaviors, such as feeling more hunger after a workout; present weight status (39); or the differential impact of sunlight on the mass of different adipose tissue types (5,15). PA levels may independently increase serum vitamin D levels.…”
Section: Original Articlementioning
confidence: 99%